Tanácsadás az ápolásban - sztereotípiák a valóságban - Boros Katalin Gyöngyi (2009)
The Act of Parliament number CLIV of 1997 stipulates that nurses must provide patients/clients with counselling as part of their patient management. However significant it is, only little research has been done on whether the conditions required for counselling are fulfilled. Thus the aim of this research was to explore the effectiveness of the principles of helping relationships and the counselling styles adopted by nurses, the results of which can be used in the development of nurse training, too. 43 third-year regular students took part in the survey and the results were analysed in 2008. The method of the research was the so called “Looking for Trap.” First, we examined the effectiveness of the principles of helping relationships. 51.2% of the student nurses define nursing in the traditional sense that is they want to help patients without involving them in the process. The expectations of the patients’ activities can be assessed by using independence premises. The premises used in the sample are incidental and vague; all the premises were fulfilled in 16.69% of the cases. When analysing nursing attitudes with model situations, we found the occurrence of restrictive patient management style had the highest proportion, 60.4%. Conclusion: both the principles and the patient management styles are found to be full of traditional stereotypes, which are still functioning in our reality and nurse training has to participate in changing this.